Should I stay or should I go? An institutional approach to brain drain - Lea Cassar; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2010)
This paper suggests that institutional factors which reward social net- works at the expenses of productivity can play an important role in ex- plaining brain drain. The e exteuroects of social networks on brain drain are analyzed in a decision theory framework with asymmetric information. We distinguish between the role of insidership and personal connections. The larger the cost of being an outsider, the smaller is the number and the average ability of researchers working in the domestic job market. Per- sonal connections partly compensate for this e exteuroect by attracting highly connected researchers back. However, starting from a world with no dis- tortions, personal connections also increase brain drain.
Keywords: D82; F22; I20; J24; J44; 330; Brain Drain; Social Networks; Institutions; Asymmetric In- formation; Italian Academia